Gamma measurement based on CMOS sensor and ARM microcontroller - Cheng, Qian-Qian; Yuan, Yan-Zhong; Ma, Chun-Wang; Wang, Fang (Nuclear science and techniques, 2017)
A setup based on CMOS sensor and ARM microcontroller is designed to measure the γ-rays. STM32F103 is used as the main platform to control real- time online analysis of the image collected by the OV7670 CAMERACHIPTM and send the image into the LCD at the desired frame rate. Accuracy of sampling interval can be regulated and controlled. The frame number of image is adjusted by STM32F103 to achieve better monitoring. Two methods are adopted to analyze the image data from the CMOS sensor. Although the CMOS sensor is of low effi- ciency for γ-ray detection, the results show that it is able to discriminate the 60Co γ-rays.